Confirmatory report of Damselfly (Odonata) Pixie Dartlet, Ischnura nursei (Morton, 1907) from Bangladesh (Bangladesh Journal of Zoology, 2023)
Abstract not availableBangladesh J. Zool. 51(1): 129-133, 2023